Hereditary angioedema plasma proteomics following specific plasma kallikrein inhibition with lanadelumab - Sexton, Dan; Kichev, Anton; Juethner, Salomé; Yeung, Dave; MacDonald, Amanda; Anokian, Ezequiel; Li, Bin (Frontiers in Immunology, 2025)
IntroductionPlasma proteomics analyses were performed to identify novel disease state biomarkers of hereditary angioedema due to C1 inhibitor deficiency (HAE-C1INH) and investigate the biological consequences of specific plasma kallikrein inhibition with lanadelumab.MethodsAffinity proteomic analyses were performed using plasma from healthy controls (n=30) and patients with HAE-C1INH before (baseline, n=125) and after 6 months of treatment with lanadelumab (300 mg every 2 weeks, n=112) using the SomaScan platform.ResultsRelative plasma levels for several proteins differed significantly between controls and patients with HAE-C1INH, and between matched baseline and post-treatment samples from patients with HAE-C1INH. As expected, C1 inhibitor and complement C4 were significantly lower (P<1.10e-39 false discovery rate [fdr], P<6.6e-25 fdr, respectively) in HAE-C1INH baseline plasma versus controls. Cleaved high-molecular-weight kininogen, a biomarker of excess kallikrein-kinin system (KKS) activation, was higher in HAE-C1INH baseline plasma versus controls (P<6.7e-6 fdr) and was reduced in HAE-C1INH plasma after lanadelumab treatment. Of 1041 identified proteins that differed significantly (P<0.05) from controls and HAE-C1INH baseline plasma, 120 proteins were no longer different between controls and patients with HAE-C1INH after 6 months of lanadelumab treatment. Canonical pathway and local network analyses of HAE-C1INH plasma proteomics suggest dysregulation in KKS, coagulation, cell adhesion, and connective tissue degradation that approach that of healthy controls following treatment with lanadelumab.ConclusionProteomic analyses of plasma from patients with HAE-C1INH before and after treatment with lanadelumab compared with healthy controls confirmed known HAE-C1INH biomarkers and identified additional potential biomarkers of plasma kallikrein dysregulation for further investigation.